IMMU-13. DUAL IGF1R/IR INHIBITOR IN COMBINATION WITH GD2-CAR T-CELLS AS A POTENT THERAPEUTIC STRATEGY FOR H3K27M-MUTANT DIFFUSE MIDLINE GLIOMAS. (4th December 2020) - de Billy, Emmanuel; pellegrino, Marsha; De Angelis, Biagio; Businaro, Pietro; Orlando, Domenico; Pericoli, Giulia; Petrilli, Lucia Lisa; Rossi, Sabrina; Ferretti, Roberta; Maestro, Nicola; Massimi, Luca; Pezzullo, Marco; et al.
Abstract: Diffuse midline gliomas (DMG) are aggressive paediatric brain tumors for which there is no effective treatment. Recent pre-clinical studies suggest that adoptive transfer of chimeric antigen receptor (CAR) T-cells targeting the disialoganglioside antigen GD2 (GD2-CAR) has a significant therapeutic potential for H3K27M-mutant DMG. Still, some tumor cells resist to treatment suggesting that a multimodal approach may be necessary to treat more efficiently the disease. Our aim was to identify chemical compounds that, in combination with CAR T-cells, would enhance anti-tumor efficacy. After having confirmed the GD2 expression in tissue samples and patient-derived H3K27M-mutant DMG cells, we developed a high throughput cell-based assay to screen 40 kinase inhibitors in combination with T-cells expressing the GD2-CAR.CD28.4-1BB.z construct. The screening led to the identification of the dual IGF1R/IR antagonists, BMS-754807 and linsitinib, which, in combination with GD2-CAR T-cells, improved antitumor activity by 25% (p<0.0001) and 20% (p<0.0001) respectively, compared to GD2-CAR T-cells alone. The two compounds inhibited tumor cell proliferation through IGF1R/IR dependent mechanisms at a concentration which did not affect CAR T-cell expansion. Linsitinib, but not BMS-754807, decreased GD2-CAR T-cells exhaustion and increased their memory profile. Furthermore, linsitinib attenuated the expression of 10 out of 71 DMG genes involved in immunomodulation ( e.g . IL33, VEGFC, STAT5A) and regulated upon tumor/CAR T-cells co-culture. Finally, we confirmed the anti-tumor activity of the new linsitinib/GD2-CAR T-cells combination strategy in a DMG H3K27M-mutant 3D culture model. Our work supports the development of IGF1R/IR inhibitors to be used in combination with GD2-CAR T-cells for H3K27M-mutant DMG therapy.